2022
DOI: 10.1007/s11356-022-20441-5
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of flavocoxid on cyclophosphamide-induced cardio and neurotoxicity via targeting the GM-CSF/NF-κB signaling pathway

Abstract: Cyclophosphamide (Cyclo) is a chemotherapeutic agent used as an immunosuppressant and as a treatment for many cancerous diseases. Many previous pieces of literature proved the marked cardio and neurotoxicity of the drug. Thus, this research provides evidence on the alleviative effect of flavocoxid on the cardiac and brain toxicity of cyclophosphamide in mice and determines its underlying mechanisms. Flavocoxid (Flavo) is a potent antioxidant and anti-inflammatory agent that inhibits the peroxidase activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Parallel to this phenomenon, this study shows that Cyclo induces an increase in the p-Akt content and eNOS protein expression, which are in line with the findings of previous reports ( Sancho et al, 2014 ; Barberino et al, 2022 ; Elsayed et al, 2022 ). The reductions of p-Akt and eNOS by TEL, free Sp, and nano Sp pretreatments are observed in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Parallel to this phenomenon, this study shows that Cyclo induces an increase in the p-Akt content and eNOS protein expression, which are in line with the findings of previous reports ( Sancho et al, 2014 ; Barberino et al, 2022 ; Elsayed et al, 2022 ). The reductions of p-Akt and eNOS by TEL, free Sp, and nano Sp pretreatments are observed in this study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, various studies demonstrated that oxidative stress elicited by cyclophosphamide in the brain is mediated through overproduction of reactive oxygen species (ROS), GSH depletion and inhibition of antioxidant enzymes activities [13,14]. In addition, it was found that the activation of angiotensin converting enzyme and the resultant excessive production of angiotensin II by cyclophosphamide has been implicated in ROS generation and hence the subsequent oxidative brain injury [15].The massive generation of ROS prompts oxidative damage to numerous cellular components resulting in lipid peroxidation, DNA damage and mitochondrial dysfunction [14,[16][17][18]. Mechanisms by which cyclophosphamide-induced oxidative stress is shown in Fig.…”
Section: Induction Of Oxidative Stressmentioning
confidence: 99%
“…Ample evidence has verified the crucial role of neuroinflammation in the development and progression of chemotherapy-associated neurological abnormalities [26,27]. Likewise, several experimental studies have implied that sustained inflammatory responses alongside the immense discharge of pro-inflammatory cytokines as tumor necrosis factor alpha (TNF-α) and interleukins are the major driving force for neurodegeneration associated with cyclophosphamide [17,23,24,[28][29][30][31]. In this regard, several inflammatory signaling cascades are considered as integral elements in the pathogenesis of neuronal inflammation induced by cyclophosphamide such as nuclear Factor kappa B (NF-κB), toll-like receptors (TLR) and the nucleotidebinding oligomerization domain (NOD)-like receptor family pyrin domain containing 3 (NLRP3) signaling pathways [24,29,32].…”
Section: Induction Of Inflammatory Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Free radicals are produced endogenously through several enzymes, such as NADPH oxidase (NOX) [97], nitric oxide synthase (NOS) [98], myeloperoxidase (MPO) [99], 5lipoxygenase (5-LOX) [100], monoamine oxidase B (MAOB) [101], xanthine oxidase [102], and cyclooxygenase [103]. However, free radical production by various enzymes is necessary for the physiological and biological functions; overproduction of such substances could produce harmful oxidative stress, which should be neutralized through antioxidant defense mechanisms or nutraceutical antioxidants [104].…”
Section: In Silico Investigations (Molecular Docking)mentioning
confidence: 99%